COMMUNICATION STRATEGIES USED BY TEACHER IN ENGLISH AS FOREIGN LANGUAGE TEACHING AND LEARNING IN NORTH BALI BILINGUAL SCHOOL - ., I Putu Agus Juli Sastrawan; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengetahui jenis-jenis strategi komunikasi yang digunakan oleh guru di kelas II Yayasan Dwi Bahasa Bali Utara dalam berkomunikasi dengan siswa, jenis strategi komunikasi yang paling sering digunakan oleh guru dan alasan guru dalam menerapkan strategi komunikasi untuk berkomunikasi dengan siswa. Subyek penelitian ini adalah guru bahasa Inggris di kelas II di Yayasan Dwi Bahasa Bali Utara. Penelitian ini menggunakan desain kualitatif. Metode pengumpulan data adalah observasi dan wawancara. Temuan menunjukkan bahwa guru menggunakan enam jenis strategi komunikasi, yaitu: approximation (10%), circumlocution (5%), clarification request (10%), comprehension check (20%), use of fillers/hesitation devices (25%) and paralanguage (30%). Paralanguage adalah strategi komunikasi yang paling sering digunakan. Dua alasan utama mengapa guru menerapkan strategi komunikasi, yaitu: strategi komunikasi membantu siswa memahami sesuatu dengan cara yang berbeda dan membantu siswa dalam memahami apa yang dikatakan.Kata Kunci : strategi komunikasi, guru, dwi bahasa This study aimed at finding out the types of communication strategies used by teacher in grade II of North Bali Bilingual School in communicating with students, the type of communication strategies used most frequently by teacher and teacher’s reasons in applying communication strategies to communicate with the students. The subject of this study was an English teacher on grade II in North Bali Bilingual School. The present study employed qualitative design. The methods of data collection were observation and interview. The findings showed that the teacher used six types of communication strategy, namely: approximation (10%), circumlocution (5%), clarification request (10%), comprehension check (20%), use of fillers/hesitation devices (25%) and paralanguage (30%). Paralanguage was the communication strategy which was used most frequently. Two main reasons why the teacher applied communication strategies were found, those are: communication strategies helped the students understand something in different way and helped the students in understanding what is being said. keyword : communication strategies, teacher, bilingual